The Role of Visual and Interactive Media in Teaching English to Elementary School Students: A Literature Review - Tiarnita Maria Sarjani Br. Siregar; Shyaillah Fadillah; Fatharisa Azzahrawani (International Education Trend Issues, 2026)
This study aims to examine the role of visual and interactive media in teaching English to elementary school students through a systematic literature review. Employing a qualitative approach, the study analyzes relevant scholarly publications from the past ten years. The findings reveal that visual and interactive media significantly contribute to enhancing students’ learning motivation, vocabulary acquisition, active participation, communication skills, and the development of meaningful learning environments. Visual media—such as images, flashcards, and videos—facilitate students’ comprehension of language concepts by presenting them in concrete and contextualized forms. Meanwhile, interactive media—including digital games and multimedia applications—encourage active engagement and collaborative learning experiences. Furthermore, the integration of these media reduces language anxiety and fosters an enjoyable classroom atmosphere. As a result, students demonstrate greater confidence in using English and increased involvement in learning activities. Therefore, the incorporation of visual and interactive media is essential for promoting effective, engaging, and meaningful English language instruction at the elementary school level.